Case Report: Patient with deficiency of ADA2 presenting leukocytoclastic vasculitis and pericarditis during infliximab treatment - Simão Raimundo, Diana; Cordeiro, Ana Isabel; Parente Freixo, João; Valente Pinto, Marta; Neves, Conceição; Farela Neves, João (Frontiers in Pediatrics, 2023)
Deficiency of adenosine deaminase 2 (DADA2), first reported in 2014, is a disease with great phenotypic variability, which has been increasingly reported. Therapeutic response depends on the phenotype. We present a case of an adolescent with recurrent fever, oral aphthous ulcers and lymphadenopathy from 8 to 12 years of age and afterward symptomatic neutropenia. After the diagnosis of DADA2, therapy with infliximab was started but after the second dose she developed leukocytoclastic vasculitis and symptoms of myopericarditis. Infliximab was switched to etanercept, with no relapses. Despite the safety of tumor necrosis factor alpha (TNF-α) inhibithors (TNFi), paradoxical adverse effects have been increasingly reported. The differential diagnosis between disease new-onset manifestations of DADA2 and side effects of TNFi can be challenging and warrants further clarification.